ANALYSIS OF THE INFLUENCE OF LEADERSHIP AND REMUNERATION SATISFACTION ON INTENTION TO LEAVE IN AN EFFORT TO REDUCE EMPLOYEE TURNOVER AT RSU X SIDOARJO - Devita Eryani Putri (Indonesian Academia Health Sciences Journal, 2025)
Background: Employee turnover is a frequent problem in organizations, various studies have been done on turnover. In a healthy organization it is not aligned with the problem of employee turnover. RSU X Sidoarjo is a class D hospital. From the survey results that have been obtained, employees who want to leave RSU X Sidoarjo because they do not match the leadership or management get a result of 71.4%, then employees want to leave RSU X Sidoarjo to look for a higher salary of 61.9% Based on the data above and data with employees who resign has been calculated using the Labor Turn Over formula it is known that 24.0% which exceeds the standard value namely 5-10% in one period. The purpose of this study is to analyze the leadership factors and remuneration satisfaction on intention to leave as an effort in employee turnover, Method: quantitative method, This study will be conducted at RSU X Sidoarjo with respondents who are still permanent employees. The population to be used in this study is 146 employees. This analysis was carried out on each research variable. Results: conclusion (1) the leadership factor at RSU X Sidoarjo was good with a result of 65.4% and not good with a result of 34.6%, while the Remuneration Satisfaction at RSU X Sidoarjo was not in accordance with the result of 58.22% and in accordance with the result of 41.78%, and the Intention to leave employees at RSU X Sidoarjo was a high desire with a result of 62.00% and a low desire of 38.00%. (2) Remuneration Satisfaction has an influence on Intention To Leave at RSU X Sidoarjo with a significance value of 0.034 while Leadership has no influence with a significance value of 0.163 (3) 2 Strategic Issues and Recommendations Related to Remuneration and Intention To Leave at RSU X Sidoarjo